1996
DOI: 10.1136/adc.75.6.482
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone and bacterial meningitis in Pakistan.

Abstract: The objective ofthis study was to assess, in a developing country setting, the effect of dexamethasone therapy on bacterial meningitis outcomes. A prospective double blind placebo controlled trial was conducted in 89 children aged from 2 months to 12 years suffering from bacterial meningitis. Neurological, developmental, and hearing assessments were conducted at one, four, and 12 months after discharge. Forty eight patients received dexamethasone and 41 placebo. Initial antimicrobial drugs used were ampicillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 23 publications
3
44
0
1
Order By: Relevance
“…An E. coli K1-strain isolated from a child with neonatal meningitis (gift of Dr. G. Zysk, Institute of Medical Microbiology, Düssel-dorf, Germany) was cultured on blood agar plates at 37°C, harvested with 0.9% saline and preserved in aliquots containing 10 10 CFU/mL at -70°C. Minimal inhibitory concentration and minimal bactericidal concentration for ceftriaxone determined by broth microdilution were 0.0625 and 0.125 mg/L, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An E. coli K1-strain isolated from a child with neonatal meningitis (gift of Dr. G. Zysk, Institute of Medical Microbiology, Düssel-dorf, Germany) was cultured on blood agar plates at 37°C, harvested with 0.9% saline and preserved in aliquots containing 10 10 CFU/mL at -70°C. Minimal inhibitory concentration and minimal bactericidal concentration for ceftriaxone determined by broth microdilution were 0.0625 and 0.125 mg/L, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In the meningitis study, however, no reduction of the frequency of neurologic sequelae after the observation period of 8 wk could be demonstrated (8). The beneficial effect of adjunctive dexamethasone treatment observed in European countries was absent under the conditions of developing countries (9,10).…”
mentioning
confidence: 96%
“…Adjuvant dexamethasone treatment did not result in an increased risk of serious adverse events, such as gastrointestinal bleeding. Studies in the developing world, where presentation to hospital is often delayed, showed that adjuvant steroid treatment could not improve outcome in this setting (96,123). These results indicate that corticosteroids are only beneficial when administered early in the course of the disease.…”
Section: Introductionmentioning
confidence: 67%
“…In another study published in 1996, Qazi et al analyzed 89 patients aged 2 months to 12 years with BM, selected from April 1990 to March 1992 in a pediatric hospital in Pakistan (26) . Children with kidney or liver disease, diseases of the central nervous system (epilepsy, hydrocephaly, previous history of meningitis, hearing loss, mental impairment) or a history of trauma were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…(22)(23)(24)(25)(26) In 2007, Peltola et al published the results of a multicenter study conducted in ten Latin American countries from 1996 to 2003, including 654 children aged 2 months to 16 years with bacterial meningitis, no previous history of traumatic brain injury (TBI) and no recent neurosurgery, neurological disease, immunosuppression or hearing impairment known (23) . The diagnosis was defined by positive cerebrospinal fluid (CSF) culture for typical BM causative agent, characteristic biochemical and cytological findings on positive CSF and blood cultures, characteristic CSF biochemical and cytological findings associated to positive latex agglutination test or signs and symptoms consistent with meningitis associated with at least three of the following criteria: CSF pleocytosis (>1000cells/mm³); hypoglycorrhachia (<40mg/dL), hyperproteinorrhachia (>40mg/dL), increased C-reactive protein serum (>40mg/L).…”
Section: Resultsmentioning
confidence: 99%